Peran Kepemimpinan Transformasional dalam Memoderasi Hubungan antara Komitmen Organisasional dan Kepuasan Kerja terhadap Organizational Citizenship Behavior - Helmi Sandy; Setiawan, Ryan Hamaeludin; Dikdik Budiawansyah; Ade Solahudin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to determine the relationship between job satisfaction to OCB and organizational commitment partially and simultaneously, by investigating the role of transformational leadership as a moderator variable at CV. Bangun Mandiri. The population of this study were all employees of CV, using testing techniques with the Smart PLS application. This study uses Measurement Model Analysis (Outer Model), Structural Model Analysis (Inner Model), and Hypothesis Testing. The results of this study indicate that Organizational Commitment and Job Satisfaction have no significant effect on OCB. In contrast, Transformational Leadership has a substantial effect on OCB but does not moderate the relationship between Organizational Commitment and Job Satisfaction with OCB. Thus, only Transformational Leadership has a direct impact on increasing OCB without strengthening other relationships.